Pro LINQ Language Integrated Query in C# 2010 - Rattz, Joseph; Freeman, Adam (Apress : Imprint: Apress, 2010)
LINQ is the part of the .NET Framework that provides a generic approach to querying data from different data sources. It has quickly become the next must-have skill for .NET developers. Pro LINQ: Language Integrated Query in C# 2010 is all about code. Literally, this book starts with code and ends with code. Most books show the simplest examples of how to use a method, but they so rarely show how to use the more complex prototypes. This book is different. Demonstrating the overwhelming majority of LINQ operators and prototypes, it is a veritable treasury of LINQ examples. Rather than obscure the relevant LINQ principles in code examples by focusing on a demonstration application you have no interest in writing, this book cuts right to the chase of each LINQ operator, method, or class. However, where complexity is necessary to truly demonstrate an issue, the examples are right there in the thick of it. For example, code samples demonstrating how to handle concurrency conflicts actually create concurrency conflicts so you can step through the code and see them unfold. Face it, most technical books, while informative, are dull. LINQ need not be dull. Written with a sense of humor, this book will attempt to entertain you on your journey through the wonderland of LINQ and C# 2010.